Formación Profesional, an effective educational response to address the right to work of our youth. (Journal of Parents and Teachers, 2014)
By linking the right to work and the duty to work recognized by our constitution, ways of fulfilling this right through the two paths (Bachillerato and Formación Profesional) offered by our educational system, considering the advantages of the Formación Profesional are discussed. But this path to be considered as secondary, both socially and in the design of the system, the convenience of the university focus its admission of students to the detriment Vocational Baccalaureate arises, giving greater recognition of the studies undertaken by these students arriving, if necessary, to redesign their curricula to align with studies consistently this way.
Keywords: Spanish educative system; right to work; effectiveness and efficiency of the education system; bachelor's degree; youth unemployment